MicroRNA signatures in peripheral blood fail to detect acute cellular rejection after liver transplantation. (16th November 2016) - Raschzok, Nathanael; Reutzel-Selke, Anja; Schmuck, Rosa B.; Tannus, Laura M.; Morgul, Mehmet H.; Dietel, Corinna; Leder, Annekatrin; Struecker, Benjamin; Lippert, Steffen; Sallmon, Hannes; Schmelzle, Moritz; Bartels, Michael; et al.
Abstract: Objective: We investigated whether microRNA signatures in whole blood samples are associated with acute cellular rejection (ACR) after liver transplantation. Materials and methods: Blood samples were collected using Paxgene technology and analyzed by microarrays and quantitative real-time polymerase chain reaction (qRT-PCR). Results: microRNA signatures failed to distinguish between 19 patients with ACR and 16 controls. Let-7b-5p and let-7c were upregulated in a subgroup of patients with ACR during the 6th and 7th postoperative days but failed in an independent validation of 20 patients. Conclusion: microRNA signatures in whole blood processed by Paxgene technology are not suited for the detection of ACR after liver transplantation.